Fish deterrent associated with bubble dispersion in bulb turbine - Silva, Tania Machado da; Figueiredo, Wllyane Silva; Santos, Alexandre Silva dos; Melo Neto, Miguel Vieira de; Zara, Luiz Fabrício (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
During the maintenance procedures of generating units, the operational maneuver of shutting down the turbine causes low water flow, which may lead to the accumulation of fish inside the draft tube. Considering the principles of ichthyofauna protection, several repulsion systems have been developed to minimize the confinement and the possible risks to the ichthyofauna. The main objective of this study was to investigate the dissuasive effectiveness on the ichthyofauna caused by the dispersion of bubbles along the draft tube during the shutdown of the generating unit. The monitoring of the ichthyofauna in the draft tube was carried out with the aid of a hydroacoustic system. The bubble dispersion procedure was executed using the compressed air injection system built into the draft tube of the Generating Units at the Jirau Hydropower Plant, on the Madeira River, in Rondônia, Brazil. 9 machine shutdowns were tracked. They were carried out in two stages; the first stage was the conventional shutdown and the second was the shutdown of the generating unit with bubble dispersion. During both stages, the movement of the confined ichthyofauna was continuously monitored by a hydroacoustic real-time monitoring system installed in the fixed-wheel gates. The results show a reduction of about 42% in the ichthyofauna movement after the bubble dispersion procedure, making it possible to infer a considerable reduction in ichthyofauna confinement in the draft tube. This observed effectiveness, in an unfavorable environment with the high turbidity of the Madeira River, shows the considerable potential of this robust and low-cost technology for the protection of ichthyofauna in the hydroelectric sector.
Keywords: Ichthyofauna deterrence; Air bubble; Behavioral effect; Madeira River